1974
DOI: 10.1159/000149744
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gross Murine Leukemia Virus Replication by Rifamycin SV and Certain of Its Derivatives in vitro

Abstract: Rifamycin SV and several of its derivatives were examined for their ability to inhibit the replication of Gross murine leukemia virus in intact Swiss mouse embryo cells growing in culture. Antiviral activity was observed with rifamycin SV, 3-formyl rifamycin SV: dipropylhydrazone and benzyl dimethyl rifampicin, when the compounds were tested against this RNA tumor virus by means of the UV-XC plaque-reduction procedure. However, several of the rifamycin derivatives which strongly inhibited the viral RNA-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Shannon el al. [42] have observed that Gross MLV infection of mouse cells is inhibited by rifamycin SV.…”
Section: Discussionmentioning
confidence: 99%
“…Shannon el al. [42] have observed that Gross MLV infection of mouse cells is inhibited by rifamycin SV.…”
Section: Discussionmentioning
confidence: 99%
“…Control experiments, in which mature Rous sarcoma virus was incubated with the drug, excluded the possibility that simple binding of the highly lipophilic drug could result in the disruption of the normal structure and consequent loss of infectivity. SHANNON et al (1974) studied the effect of rifamycin SV and several strong inhibitors of the reverse transcriptase on Gross virus replication in NIH Swiss mouse 542 murine lymphoma. It was suggested that R-8 z, an inhibitor of polymerases, might interfere with viral RNA transcription.…”
Section: H Friedman and S Spectermentioning
confidence: 99%
“…Inhibition of cell transformation and/or oncornavirus replication by rifamycin derivatives has been reported by several laboratories (Barlati and Vigier, 1972;Ting et al, 1972;Green et al, 1972Green et al, , 1974Bissel et al, 1974;Smith and Hackett, 1974;Shannon et al, 1974; Szabo et al, 1976). Thus far, it appears that when cytotoxic effects are avoided the antiviral activity observed may be the result of the inhibition of the reverse transcriptase and/or interference with other postpenetrational viral functions.…”
mentioning
confidence: 95%